Interferon gamma gene polymorphisms and chronic hepatitis B infections in an Iranian population - Heidari, Zahra; Moudi, Bita; Mahmoudzadeh-Sagheb, Hamidreza (Turkish Journal of Gastroenterology, 2020)
Background and Aims: Chronic hepatitis B is an important health problem in all countries. I Interferon gamma is a pro-inflammatory Th1 cytokines, which can exert antiproliferative and antitumor activity. Some SNPs in IFN-γ and IFN-γR1 genes may influence the susceptibility to HBV. Here, we evaluated the impact of interferon gamma (+874 T/A) and its receptor (-611A/G, +189G/C and +95C/T) polymorphisms and the risk of HBV in Iranian patients. Materials and Methods: SNPs of interferon gamma and its receptor genotypes were determined in 221 infected patients with HBV and 200 people without HBV using ARMS-PCR and PCR- RFLP method. Results: In this study, we showed an obvious relationship between IFN-γ SNPs and susceptibility to chronic HBV. Our findings suggest that IFN-γ-874A allele increases the risk of disease and carriers of the T allele have reduced susceptibility to infection. In addition, there was not any relationship between the -611A/G, +189G/C and +95C/T regions of IFN-γ R1 and HBV. Conclusions: Our observations demonstrate +874 T/A SNP as a predicting factor in patients who have the risk of HBV.